A new stiletto fly genus from South America (Diptera: Therevidae: Agapophytinae) - Irwin, Michael E.; Winterton, Shaun L. (Zootaxa, 2020)
The South American members of the stiletto fly subfamily Agapophytinae (Diptera: Therevidae) comprise three genera that occur predominantly in the western region. Here we describe a newly discovered genus, Sigalopella gen. n., from Chile containing four new species.